Morphological and SRAP-based genetic diversity analysis of Zinnia elegans Jacq. accessions - Sari, Miranda Ferwita; Purwantoro, Aziz; Purwestri, Yekti Asih; Sulistyaningsih, Endang (Ornamental Horticulture, 2025)
Zinnia elegans Jacq. is ornamental plant commonly cultivated in Indonesia. This species has various flower shapes and colors and is easy to be cultivated in any environmental conditions. This study aimed to determine the genetic diversity of 18 Z. elegans accessions based on morphological and SRAP molecular markers. The research was arranged a completely randomized design (CRD) with 18 accessions as treatments and three replications within each treatment. SRAP analysis was performed using five primer combinations of C1 (Me6-Em6), C2 (Me8-Em4), C3 (Me8-Em7), C4 (Me9-Em4), and C5 (Me10-Em4). Meanwhile, Z. elegans descriptor from UPOV was used in morphological analysis for quantitative and qualitative traits. The result showed a dendrogram with two main branches of group A and B for morphological traits and SRAP markers with a similarity coefficient of 0.18- 0.78 and 0.46-0.80, respectively. SRAP markers significantly correlated with six morphological traits, such as ray floret apex (RFA), ray floret length (RFL), leaf length (LL), leaf width (LW), stem length (SL), and ray floret width (RFW). Five morphological traits that had high GCV and strong SRAP correlation were prioritized for selection. Five SRAP combination primers can be used for molecular marker resources of Zinnia breeding.